2011
DOI: 10.1242/dev.072454
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear trapping by GL3 controls intercellular transport and redistribution of TTG1 protein inArabidopsis

Abstract: SUMMARYTrichome patterning on Arabidopsis leaves is one of the best-studied model systems for two-dimensional de novo patterning. In addition to an activator-inhibitor-related mechanism, we previously proposed a depletion mechanism to operate during this process such that GLABRA3 (GL3) traps the trichome-promoting factor TRANSPARENT TESTA GLABRA1 (TTG1) in trichomes that, in turn, results in a depletion of TTG1 in trichome neighbouring cells. In this manuscript we analyze the molecular basis underlying this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 48 publications
1
58
0
Order By: Relevance
“…A functional NLS is sufficient to overcome the NESmediated nuclear export resulting in activation of the LEUCINE2 (LEU2) reporter gene. Using the NTT assay we found that AtMYC1, in contrast to GL3 (Balkunde et al, 2011), could not activate the LEU2 reporter, indicating that it does not contain a functional NLS. Significantly, additional expression of TRY or CPC led to the activation of LEU2, whereas co-expression of GL1 did not activate the reporter.…”
Section: Research Article Development 140 (16)mentioning
confidence: 89%
See 2 more Smart Citations
“…A functional NLS is sufficient to overcome the NESmediated nuclear export resulting in activation of the LEUCINE2 (LEU2) reporter gene. Using the NTT assay we found that AtMYC1, in contrast to GL3 (Balkunde et al, 2011), could not activate the LEU2 reporter, indicating that it does not contain a functional NLS. Significantly, additional expression of TRY or CPC led to the activation of LEU2, whereas co-expression of GL1 did not activate the reporter.…”
Section: Research Article Development 140 (16)mentioning
confidence: 89%
“…Patterning genes were introduced by LR recombination with the respective entry clones. The plasmid vector pNS and pNS-GL3 were described previously (Ueki et al, 1998;Balkunde et al, 2011). AtMYC1 CDS was cloned as a SalI-HindIII fragment from SalI-AtMYC1-HindIII-pGEM-T-easy (supplementary material Table S3) into the SalI site of pNS to create pNS-AtMYC1 (supplementary material Table S3).…”
Section: Yeast Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intercellular interactions are mediated by the inhibitors. Second, TTG1 is trapped in incipient trichome cells by GL3 and thereby depleted from the surrounding cells (Bouyer et al, 2008;Balkunde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the root system, GL3 was shown to be expressed in root hair files, from where it moves to the nonroot hair files (Bernhardt et al, 2005). In leaves, TTG1 movement occurs from nontrichome cells to trichomes (Bouyer et al, 2008;Balkunde et al, 2011).…”
mentioning
confidence: 99%